Thermo-Hydraulic Optimization of Shell and Externally Finned Tubes Heat Exchanger by the Thermal Efficiency Method and Second Law of Thermodynamics - Nogueira, Elcio (International Journal of Chemical and Process Engineering Research, 2022)
The application aims to determine the thermal and hydraulic performance of externally finned, counter-flow, Shell, and Tube Heat Exchangers (STHE). The application refers to the cooling of machine oil flowing in the annular region, including non-spherical cylindrical nanoparticles of Boehmite Alumina. The oil inlet temperature is equal to 80 °C. Sea water is a coolant with an inlet temperature of 20°C. The main parameter in the optimization process is the number of finned tubes used for oil cooling. Another optimization factor is the number of heat exchanger units connected by hairpin. The number of fins per tube is fixed, equal to 34. The oil flow is set and equal to 4.0 kg/s. The inlet water flow varies, with a maximum flow of 5.0 kg/s. The quantities determined for analysis are: the thermal effectiveness, the actual and maximum heat transfer rates, the pressure drops caused in the tubes and by the flow in the annular region and fin system, the thermal and viscous irreversibilities, and the fluid outlet temperatures, and the thermodynamic Bejan number. It was determined that increasing the number of finned tubes from two to six tubes leads to better thermal and hydrodynamic performance. That is, it produces a favorable cost-benefit, to the detriment of the high viscous dissipation caused by the oil in the annular region. As an object of analysis, the inclusion of nanoparticles showed a significant improvement in thermal performance and an increase in viscous dissipation, with a slight decline in the Bejan number.